Effect of Steel Fibres Distribution on Impact Resistance Performance of Steel Fibre Reinforced Concrete (SFRC) - Muda Z.C.; Kamal N.L.M.; Syamsir A.; Yang C.S.; Beddu S.; Mustapha K.N.; Thiruchelvam S.; Usman F.; Itam Z.; Alam M.A.; Birima A.H.; Zaroog O.S. (Institute of Physics Publishing, 2023)
Concrete slabs; Concretes; Cracks; Drops; Fiber reinforced materials; Fibers; Mesh generation; Reinforced concrete; Shotcreting; Crack resistance; Drop weight impact; Impact performance; Impact resistance performance; Mesh distributions; Projectile tests; Slab thickness; Steel fibre reinforced concrete; Steel fibers; absorption; crack; impact structure; performance assessment; reinforced concrete; reinforcement; research work; steel; stress resistance